IDENTIFICATION AND MEASUREMENT OF INTANGIBLE ASSET VALUE: ESTIMATING AND ACCOUNTING APPROACHES - T. P. Karpova; V. V. Karpova (Финансы: теория и практика, 2017)
The paper presents a comprehensive view of the problem of identifying and measuring the value of intangible assets (IA) and intellectual property (IP) objects. The main approaches to the formation of the intangible asset definition in Federal Valuation Standards (FVS), International Financial Reporting Standards (IFRS) and the Russian Accounting Standards (RAS) are analyzed. It is noted that the current system of Russian federal standards for valuation, accounting and reporting contains fragmentary norms for individual components of the objects involved. There are contradictions between the volumes and the criteria for recognizing the results of intellectual activity in civil circulation and the accounting system. The authors outlined three blocks of problems of the observed gap between the indices of accounting and the market capitalization of the company: the lack of an active market, which makes it impossible to measure the external market value of the IA; the lack of proper regulation of individual intellectual property institutions; Unreliability of the IA value reflected in financial statements; the impossibility of regarding an object as an intangible asset due to the lack of documentary confirmation of the cost component of its value. The above problems can be eliminated, in the authors’ opinion, by unidirectional coordinated actions of the professional community and regulators in the field of creating an open intellectual property market. The success of the intellectual property market depends on the quality of the tools used by market players; in particular, it concerns the achievement of a higher level of formalization of methods and methodologies for measuring the market value of intangible assets and intellectual property, both at the stage of their recognition as an asset and at subsequent disclosure of respective information in the reporting. The accounting system, in turn, should provide users with reliable information about the IA value by expanding the list of objects that can be recognized in the accounting system as intangible assets, changes in approaches to the formation of their initial value and subsequent re-valuation.